Correction: The polarization-dependent anisotropic Raman response of few-layer and bulk WTe2 under different excitation wavelengths. Issue 17 (8th February 2017) - Song, Qingjun; Wang, Haifeng; Xu, Xiaolong; Pan, Xingchen; Wang, Yilun; Song, Fengqi; Wan, Xiangang; Dai, Lun
Abstract : Correction for 'The polarization-dependent anisotropic Raman response of few-layer and bulk WTe2 under different excitation wavelengths' by Qingjun Song et al., RSC Adv., 2016, 6, 103830–103837.